Efektifitas Lama Perendaman Air Kelapa Muda Terhadap Pertumbuhan Benih Pinang (Area catechu L) - Samsul Bahri; Hermanto; Agus Santoso (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
This study was to determine the length of time soaking in young coconut water was the most effective against the growth of areca seeds. The method used in this study was a non-factorial completely randomized design (CRD) consisting of six treatments with four replications. The treatments are as follows R0: Without immersion, R1: Immersion for 8 hours R2: Immersion for 16 hours, R3: Immersion for 24 hours R4: Immersion for 32 hours R5: Immersion for 40 hours. So that 24 experimental units were obtained with 4 samples of each plant seed, so that 96 samples of plant seeds were obtained. The results showed that the best treatment was immersion for 24 hours and the lowest was in the treatment without immersion.